The clinical communication and information challenges associated with the psychosexual aspects of prostate cancer treatment. (July 2017) - Speer, Susan A.; Tucker, Samantha R.; McPhillips, Rebecca; Peters, Sarah
Abstract: Rationale: Prostate cancer and its treatment have significant sexual side effects that necessitate timely patient information and open communication with healthcare professionals. However, very little is known about men's experiences of talking to clinicians about the psychosexual difficulties associated with the disease. Objective: This study aims to advance understanding of men's perceptions of the communication and information challenges associated with the psychosexual aspects of prostate cancer and its treatment. Method: Between October 2013 and April 2014, semi-structured interviews were conducted with 21 men from the UK who had been treated for prostate cancer. Interview transcripts were analysed using thematic analysis. Results: Three themes describe the communication challenges men face: (1) It can be too soon to talk about sex; (2) the psychology of sex is missing; (3) communication is not individually tailored. Conclusions: Clinicians might usefully (1) consider and discuss with patients how their psychosexual communication needs and information processing abilities may fluctuate across the cancer timeline; (2) initiate discussions about the consequences of treatment that extend beyond biological and mechanical aspects to include emotional and relational factors; (3) tailor communication to the dynamic mix of attributes that shape men's individual psychosexual needs, including their relationship status, sexual orientation, sexual motivations and values. Skills-based training in communication and psychosexual awareness may facilitate the proactive and permissive stance clinicians need to discuss sexual side effects with a heterogeneous group of patients. Highlights: Study examines the psychosexual challenges faced by men with prostate cancer. Thematic analysis of 21 interviews with men who have undergone active treatment. Three psychosexual communication challenges are identified. Challenges relate to lack of individualised, contextually-based communication. Findings recommend communication that is sensitised towards men's individual needs.